2021
DOI: 10.1038/s41531-021-00221-7
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide association study identifies susceptibility genes for Parkinson’s disease

Abstract: Genome-wide association study (GWAS) has seen great strides in revealing initial insights into the genetic architecture of Parkinson’s disease (PD). Since GWAS signals often reside in non-coding regions, relatively few of the associations have implicated specific biological mechanisms. Here, we aimed to integrate the GWAS results with large-scale expression quantitative trait loci (eQTL) in 13 brain tissues to identify candidate causal genes for PD. We conducted a transcriptome-wide association study (TWAS) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…Whole transcriptome analysis is typically based on gene or exon annotation; quite seldom transcript-based annotation is used. 26,27 Gene-based annotation is an amalgamated approach where the reads mapping to different exons and transcripts will be merged under a single functional identifier, the gene. 28 This approach is the most widely used and therefore most of the whole transcriptome studies provide this aggregated information.…”
Section: Discussionmentioning
confidence: 99%
“…Whole transcriptome analysis is typically based on gene or exon annotation; quite seldom transcript-based annotation is used. 26,27 Gene-based annotation is an amalgamated approach where the reads mapping to different exons and transcripts will be merged under a single functional identifier, the gene. 28 This approach is the most widely used and therefore most of the whole transcriptome studies provide this aggregated information.…”
Section: Discussionmentioning
confidence: 99%
“…LRRC37A2 is a member of the LRRC37 gene family which is involved in the regulation of protein–ligand interactions and mapped to chromosome 17q21.31-q21.32 ( Giannuzzi et al, 2013 ). Several studies suggested that LRRC37A2 is implicated in epilepsy, epileptic encephalopathy, and Parkinson’s disease, while the effect on DLBCL has never been reported ( Yao et al, 2021 ). In this study, high expression of LRRC37A2 corresponds with an inferior survival outcome that merits further exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, Li et al identified 66 genes whose predicted expression or splicing levels in the dorsolateral prefrontal cortex (DLFPC) and peripheral monocytes are significantly associated with Parkinson's disease (PD) risk (Li, Wong, Humphrey, & Raj, 2019). Additionally, considering the essential role of epigenetic features in predicting gene expression, Yao et al developed an epigenetic elementbased TWAS considering both genetic and epigenetic effects on gene expression as a powerful method to identify specific genes and mechanisms that underlie PD genetic risk factors (Yao et al, 2021). Applying the same idea to integrate pQTL results, Wingo et al performed a brain proteome-wide association study and implicated novel proteins in depression pathogenesis (Wingo et al, 2021b).…”
Section: Application Of Xqtlsmentioning
confidence: 99%
“…Additionally, considering the essential role of epigenetic features in predicting gene expression, Yao et al. developed an epigenetic element‐based TWAS considering both genetic and epigenetic effects on gene expression as a powerful method to identify specific genes and mechanisms that underlie PD genetic risk factors (Yao et al., 2021). Applying the same idea to integrate pQTL results, Wingo et al.…”
Section: Strategic Approachmentioning
confidence: 99%